(untitled) (Kinesiology, 2021)
The purpose of this study was to investigate the effects of six weeks of small-sided games (SSG), speed endurance (SER) and combined SSG and SER (CT) training programs on sprint, repeated sprint, Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1) and level 2 (Yo-Yo IR2) performance in young soccer players. Forty-one elite young soccer players (body height: 174.0 ± 7.5 cm, body weight: 59.7 ± 9.5 kg, age: 14.6 ± 0.5 years, training age: 7.4 ± 0.6 years) underwent anthropometric measurements before performing 10m and 30m sprint tests, repeated sprint tests, and Yo-Yo IR1 and Yo-Yo IR2. The players were then divided into four groups: the SSG group (SSG; n=11), the SER group (SER; n=10), the CT group (CT; n=11), and the control group (CG; n=9). All groups performed training for six weeks on two days out of the five training days the participants were undertaking. There was a statistically significant increase in the Yo-Yo IR1 and Yo-Yo IR2 test performances of players in SSG, SER and CT groups (p<.05). In addition, players in these groups showed significantly higher percentage increases in Yo-Yo IR2 test performance compared to the CG. The CT group also had a statistically significant increase in Yo-Yo IR1 test performance compared to the CG (p<.05). In conclusion, while this study shows that SSG and SER training can be used for physical performance development in isolation or in combination, coaches and sports scientists are advised to choose combined training to use training time more efficiently. Key words: football, interval training, game-based training, Yo-Yo intermittent recovery tests